TRENDS OF PROFESSIONAL TRAINING IN CIRCULAR ECONOMY IN THE REPUBLIC OF POLAND - Oleksii Sysoiev (Borys Grinchenko Kyiv Metropolitan University, 2022)
The article reveals the trends of professional training of circular economy specialists in the Republic of Poland. Such trends include: the creation of a legal framework for the development of the circular economy and the training of specialists in the circular economy, the implementation of financing projects that support the development of the circular economy, in particular the training of specialists for the implementation of circular economy models, the interdependence of the development of economic theory and the content of practical training of specialists in circular economy, education of children, youth and the entire population of the country regarding their role in environmental protection, the diversity of subjects involved in the training of circular economy specialists, the priority of postgraduate education in the training of circular economy specialists, the diversification of circular economy education forms and methods, deployment of professional training on the circular economy in higher education institutions, provision of practice-oriented training using both educational projects and projects on specific production (production projects), selection for forms development of the content component of the professional training of circular economy specialists in the priority sectors of circular economy implementation in the Republic of Poland, training specialists to apply circular economy business models. It was concluded that taking into account the trends of professional training of specialists in the circular economy in the Republic of Poland is of great importance for the recovery of the economy of Ukraine, as they indicate directions and ways of achieving goals based on the experience of European countries.